Method for repeatedly self-repairing damaged area of film by utilizing laser-induced graphene

By spin-coating a carbon coating on the surface of the nickel matrix and using laser to form a graphene film, the problem of easy damage of the graphene coating is solved, and multiple self-repairs of the graphene film are achieved, reducing the cost of metal protection and improving the protection effect.

CN119710688APending Publication Date: 2025-03-28SHAANXI UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411928978.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing metal protection technology has problems such as high cost, environmental pollution and limited application environment, and the graphene coating is prone to damage, making it impossible to achieve sustainable protection.

Method used

By spin-coating a carbon coating on the surface of the nickel matrix and using laser radiation to form a graphene film, multiple laser irradiation and mechanical polishing methods are used to achieve in-situ growth and self-healing of the graphene film.

Benefits of technology

Multiple self-repairs of graphene films have been achieved, which significantly reduces the cost of metal protection, improves the protection effect, and reduces environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710688A_ABST
    Figure CN119710688A_ABST
Patent Text Reader

Abstract

The invention discloses a method for repeatedly self-repairing a damaged area of a thin film by utilizing laser-induced graphene, and belongs to the technical field of metal protection. The method comprises the steps that a graphene film and in-situ self-repairing graphene grow on the metal surface in situ through laser, laser induction is adopted to simulate high-energy heat generated by a material during frictional wear, and the self-repairing graphene film formed through laser induction is destroyed in an artificial grinding and polishing mode. The number of layers, the crystallinity and the surface appearance of graphene are improved by changing the processing number, the laser power, the laser time and the like, so that the number of growth times of the laser-induced self-repairing graphene film reaches the limit. The metal protective agent is used for protecting metal materials, can remarkably prolong the service life of the metal materials, can remarkably improve the performance of the metal materials, reduces resource waste, has the characteristic of environmental friendliness, remarkably reduces the metal protection cost, and remarkably prolongs the metal protection time. The method is expected to be widely applied to extreme working environments such as aerospace, automobile manufacturing and ocean engineering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal protection, and in particular relates to a method for self-repairing a damaged area of ​​a thin film multiple times by using laser-induced graphene. Background Art

[0002] With the continuous construction of infrastructure in various countries, the demand for metal materials is increasing, but metal materials are inevitably damaged during service, such as corrosion and oxidation between the external environment, and wear between reciprocating mechanical parts. Metal corrosion is a slow chemical or electrochemical process that causes metal materials to self-destruct by interacting with oxygen and water. The losses caused by metal corrosion are huge, such as bridge collapse, shipwreck and damage to factory equipment. Traditional metal protection technologies include cathodic protection, corrosion inhibitor protection, metal coating and surface organic coating, but these methods have problems such as high cost, environmental pollution and limited application environment. Graphene, as the thinnest protective coating, exhibits excellent performance in all aspects and has attracted widespread attention due to its excellent mechanical, electrical, thermal and chemical properties brought by its unique two-dimensional layered structure. Its strength is 130 GPa, which is 100 times that of steel. It is the strongest material at present. It can be used as an additive to improve the hardness of the substrate, amazing carrier mobility and outstanding thermal conductivity. Therefore, graphene has great research value in the field of metal protection.

[0003] In recent years, with the continuous development of advanced functional materials and nanotechnology, the development of new energy devices has become possible, and the processing technology of materials and devices has faced new opportunities and challenges. For energy devices, traditional processing methods and modification processes cannot accurately control the devices. Laser processing has high energy density and small thermal impact. It can design and process specific micro-nano structures on the surface of various materials, which is conducive to the integration of devices. Therefore, research on laser processing of graphene has broad application prospects and value. In the actual production process, there are often situations where large-scale mechanical equipment cannot or is inconvenient to disassemble, repair, and replace parts. At present, most graphene anti-friction coating research only combines graphene as an independent coating with a metal substrate. Due to its nano-scale thickness, graphene cannot provide sustainable protection as a surface coating. Once these coatings are damaged, they will not be able to continue to serve to protect metal materials, which will greatly increase the cost of metal protection.

[0004] In view of the limitations of traditional metal protection technology and the fragility of graphene coatings, it is necessary to find a new method of using graphene surface coatings for metal protection to achieve effective and sustainable protection of graphene on metal surfaces, thereby reducing the cost of metal protection and improving the protection effect. Summary of the invention

[0005] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a method for multiple self-repair of film damaged areas using laser-induced graphene, so as to solve the technical problem of how to achieve in-situ growth and self-repair of graphene film on metal surface, so as to reduce the cost of metal protection and significantly improve the protection effect.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions: The present invention discloses a method for self-repairing a damaged area of ​​a thin film multiple times by using laser-induced graphene, comprising the following steps: A carbon coating is spin-coated on the surface of the pretreated nickel substrate, and a laser irradiation is performed once and a protective gas is blown sideways. After drying, a layer of graphene film is formed. The graphene film is mechanically ground, polished, cleaned and dried, and then a secondary laser irradiation is introduced under vacuum conditions to obtain a regrown graphene / nickel-based composite material. The above steps are repeated until no graphene / nickel-based composite material can be obtained after laser irradiation. The surface morphology changes of the graphene at each growth number are explored by conducting oxidation resistance tests and film-base bonding strength tests on the graphene at each growth number, and the self-repair of the damaged area of ​​the graphene film is determined.

[0007] Preferably, the step of pre-treating the surface of the nickel substrate comprises: mechanically grinding and polishing the surface of the nickel substrate with 400-2500 mesh sandpaper until it is smooth, then ultrasonically cleaning and drying.

[0008] Preferably, The preparation method of the carbon coating comprises: dissolving graphite powder in ethanol to form a dispersion, and evenly spin-coating the dispersion after ultrasonication on the surface of the nickel substrate to obtain the carbon coating, adding 10-16 mL of ethanol to every 1-1.5 g of nanographite powder; 2 Spin coat 1-3 mL of the dispersion onto the nickel substrate.

[0009] Preferably, the drying time is 5-15 min; the protective gas is argon, and the introduction time of the protective gas is 40-60 min.

[0010] Preferably, during one laser irradiation, the spot size of the laser beam is 43-65 μm, the laser power is 1000-2000 W, the scanning speed is 1-25 mm / s, and the number of processing times is 1-3 times.

[0011] Preferably, the mechanical polishing uses 400-2500 mesh sandpaper to mechanically polish the surface of the graphene film.

[0012] Preferably, when the secondary laser irradiation is introduced, argon gas is introduced for 40-60 min, and the flow rate is controlled at 160-200 mL / min.

[0013] Preferably, during the secondary laser irradiation, the spot size of the laser beam is 43-65 μm, the laser power is 21-30 W, the scanning speed is 5-25 mm / s, and the number of processing times is 1-3 times.

[0014] Preferably, the oxidation resistance test method comprises: heating the temperature to 400-450° C. at a heating rate of 1-1.5° C. every 5 minutes, and keeping the temperature for 0.5-2 hours.

[0015] Preferably, the membrane-based bonding strength test comprises: subjecting the graphene of each growth number to ultrasonic treatment for 2-10 min.

[0016] Compared with the prior art, the present invention has the following beneficial effects: The present invention discloses a method for self-repairing film damaged areas multiple times by using laser-induced graphene. The method uses laser to grow graphene film in situ on the metal surface and self-repair graphene in situ, uses laser induction to simulate the high-energy heat generated by friction and wear of the material, and destroys the self-repairing graphene film formed by laser induction by artificial grinding and polishing, and explores the growth limit of the self-repairing graphene film. The cost of metal protection is significantly reduced, and the metal protection time is significantly improved. The method can inject rich carbon sources into the substrate body. Once the surface graphene is damaged, there is no need to directly physically contact the damaged area. The use of laser-induced repair reduces the possibility of further damage and simplifies the repair process. The laser can be accurately focused on the specific position to be repaired, and effective treatment of tiny areas or even nano-level damage is achieved, which improves the repair efficiency and accuracy. Compared with traditional self-repairing materials that may take a long time to complete the repair process, laser-induced self-repair can often be completed quickly in a short time, which speeds up the overall repair speed. If the graphene film is damaged again, it can be repaired multiple times by the same laser processing method without significantly affecting the basic properties of the material, thereby enhancing the service life of the material. (In addition to self-repair, other additional functions can be given to the material by adjusting the laser parameters, such as enhancing its conductivity, improving surface hydrophilicity / hydrophobicity, etc., making it more suitable for use as a multifunctional composite material. Compared with some chemical repair methods, the laser-induced self-repair process adopted by the present invention is more environmentally friendly, reduces the use of harmful chemicals, and generates less waste, which is in line with the concept of green environmental protection and sustainable development. The present invention is used for the protection of metal materials, which can significantly improve the service life and performance of metal materials, reduce resource waste and has environmentally friendly characteristics. It is expected to be widely used in extreme working environments, such as: aerospace, automobile manufacturing, marine engineering, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a schematic diagram of a method for self-repairing a damaged film region multiple times by using laser-induced graphene according to Example 1 of the present invention; Figure 2 The Raman spectrum of the self-repairing graphene disclosed in Example 2 of the present invention; wherein (a) is the self-repairing graphene grown twice; (b) is the self-repairing graphene grown three times; (c) is the self-repairing graphene grown four times; (d) is the self-repairing graphene grown five times; (e) is the self-repairing graphene grown six times; (f) is the Raman spectrum of graphene; Figure 3 The SEM images of the self-repairing graphene before and after oxidation disclosed in Example 3 of the present invention; wherein, (a) is before the first growth oxidation; (b) is after the first growth oxidation; (c) is before the second growth oxidation; (d) is after the second growth oxidation; (e) is before the third growth oxidation; (f) is after the third growth oxidation; (g) is before the fourth growth oxidation; (h) is after the fourth growth oxidation; (i) is before the fifth growth oxidation; (j) is after the fifth growth oxidation; Figure 4 The optical microscope images of graphene at various growth times before and after ultrasonic vibration treatment in Example 3 of the present invention; wherein, (a) is before the first growth ultrasound; (b) is the first growth ultrasound for 2 minutes; (c) is the second growth ultrasound for 5 minutes; (d) is the second growth ultrasound for 10 minutes; (e) is before the second growth ultrasound; (f) is the second growth ultrasound for 2 minutes; (g) is the second growth ultrasound for 5 minutes; (h) is the second growth ultrasound for 10 minutes; (i) is before the third growth ultrasound; (j) is the third growth ultrasound for 2 minutes; (k) is the third growth ultrasound for 5 minutes; (l) is the third growth ultrasound for 10 minutes; (m) is before the fourth growth ultrasound; (n) is the fourth growth ultrasound for 2 minutes; (o) is the fourth growth ultrasound for 5 minutes; (p) is the fourth growth ultrasound for 10 minutes; (q) is before the fifth growth ultrasound; (r) is the fifth growth ultrasound for 2 minutes; (s) is the fifth growth ultrasound for 5 minutes; (t) is the fifth growth ultrasound for 10 minutes. DETAILED DESCRIPTION

[0018] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0019] In the present invention, unless otherwise specified, all the embodiments and preferred implementation methods mentioned herein can be combined with each other to form a new technical solution.

[0020] In the present invention, unless otherwise specified, all technical features and preferred features mentioned herein can be combined with each other to form a new technical solution.

[0021] In the present invention, unless otherwise specified, percentage (%) or part refers to the weight percentage or weight part relative to the composition.

[0022] In the present invention, unless otherwise specified, the components or preferred components involved can be combined with each other to form a new technical solution.

[0023] In the present invention, unless otherwise specified, the numerical range "a~b" represents an abbreviation of any real number combination between a and b, where a and b are real numbers. For example, the numerical range "6~22" means that all real numbers between "6~22" have been listed in this document, and "6~22" is just an abbreviation of these numerical combinations.

[0024] The “range” disclosed in the present invention is in the form of a lower limit and an upper limit, which can be one or more lower limits, and one or more upper limits, respectively.

[0025] In the present invention, the term "and / or" used herein refers to any combination and all possible combinations of one or more of the associated listed items, and includes these combinations.

[0026] In the present invention, unless otherwise specified, each reaction or operation step can be carried out sequentially or in accordance with the sequence. Preferably, the reaction method herein is carried out sequentially.

[0027] Unless otherwise specified, the professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any method or material similar or equivalent to the described content may also be applied to the present invention.

[0028] The present invention provides a method for self-repairing a damaged area of ​​a thin film multiple times by using laser-induced graphene, and the method is implemented according to the following steps: Step 1: Laser in-situ growth of graphene and carbon source implantation.

[0029] First, the surface of the nickel substrate is mechanically polished to remove oxides, and then a carbon coating is spin-coated on the surface after washing and drying; finally, the nickel substrate coated with a solid carbon source is irradiated with a laser once, supplemented by side-blowing argon protective gas. After the laser is removed from the laser irradiation area, a layer of graphene film is formed on the surface, and a large amount of carbon source is implanted in the nickel substrate as a self-repairing base material.

[0030] In step 1, the spot size of the laser beam of a laser irradiation is 43-65 μm, the laser power is 1000-2000 W, the scanning speed is 1-25 mm / s, and the number of processing times is 1-3 times. The laser parameters have a great influence on the laser in-situ growth of graphene film. It is necessary to use orthogonal experiments to optimize the laser power, scanning speed, processing parameters and other parameters. The carbon source is a high-purity graphite powder-ethanol dispersion with a ratio of 1-1.5 g nanographite powder: 10-16 mL ethanol. The matrix is ​​a pure nickel plate with a purity of 99.50% and a size of 80×80×5 mm. 3 ; Each 80×80 mm 2 1-3 mL of dispersion was spin-coated on the nickel substrate. After the laser was removed, the laser irradiated area was dried for 5-15 minutes, and a layer of graphene film was formed on the surface.

[0031] Step 2: Laser-induced graphene self-repair multiple times.

[0032] The original graphene film is mechanically polished by cross grinding method, and then polished by polishing machine to completely destroy the graphene film, thereby simulating the extreme situation of friction and wear of the graphene grown once on the nickel-based surface. After the polished sample is washed and dried, a secondary laser irradiation is introduced under vacuum conditions to obtain the regrown graphene / nickel-based composite material. The above process is repeated many times until the graphene / nickel-based composite material cannot be obtained after laser irradiation.

[0033] In step 2, the spot size of the laser beam of the secondary laser irradiation is 43-65 μm, the laser power is 21-30 W, the scanning speed is 5-25 mm / s, and the number of processing times is 1-3 times. When the secondary laser irradiation is introduced, argon gas is introduced for 40-60 min, and the flow rate is controlled at 160-200 mL / min.

[0034] Step 3: Self-healing graphene performance test.

[0035] Oxidation resistance: The graphene of different growth times was treated in a muffle furnace to investigate the surface morphology of graphene of different growth times, the peak shape and peak position changes of the characteristic peaks in the Raman spectrum, and the changes in the O content in the surface EDS spectrum.

[0036] Membrane-base binding strength: Graphene of different growth times was treated by ultrasound in water. After stabilization, the changes in the surface morphology of graphene of different growth times were investigated.

[0037] In the performance test in step 3, the anti-oxidation performance test: the graphene of each growth number is treated in a muffle furnace, and the treatment conditions are to heat the sample to 400-450 ℃ at a heating rate of 1-1.5 ℃ every 5 minutes, and then keep it in static air for 0.5-2 hours, take out the sample, and weigh it. Membrane-based bonding performance test: the graphene of each growth number is treated by ultrasound. The treatment conditions are ultrasound for 2 min, 5 min, and 10 min.

[0038] The self-healing graphene film prepared by the above scheme has the following advantages: (1) Non-contact repair and local precision control: This method can inject rich carbon sources into the substrate body. Once the surface graphene is damaged, there is no need to directly physically contact the damaged area. The use of laser-induced repair reduces the possibility of further damage and simplifies the repair process. The laser can be precisely focused on the specific location to be repaired, achieving effective treatment of tiny areas or even nano-level damage, improving the repair efficiency and accuracy. (2) Fast response and strong repeatability: Compared with traditional self-healing materials that may take a long time to complete the repair process, laser-induced self-repair can often be completed quickly in a short time, speeding up the overall repair speed. If the graphene film is damaged again, it can be repaired multiple times by the same laser treatment method without significantly affecting the basic properties of the material, thereby enhancing the service life of the material. (3) Multifunctional integration: In addition to self-repair, other additional functions can be given to the material by adjusting the laser parameters, such as enhancing its conductivity, improving surface hydrophilicity / hydrophobicity, etc., making it more suitable for use as a multifunctional composite material. (4) Environmental friendliness and sustainability: Compared with some chemical repair methods, the laser-induced self-repair process adopted in the present invention is more environmentally friendly, reduces the use of harmful chemicals, generates less waste, and is in line with the concepts of green environmental protection and sustainable development.

[0039] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. The components of the embodiments of the present invention described and shown in the drawings here can usually be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the claimed invention, but merely represents selected embodiments of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0040] Example 1 A method for self-repairing a damaged area of ​​a thin film multiple times by using laser-induced graphene comprises the following steps: (1) Substrate pretreatment The surface of the initial nickel block was mechanically polished with sandpaper of 400, 800, 1000, 1200, 1500, 2000 and 2500 meshes in sequence until it was smooth, then ultrasonically cleaned, and finally dried for use. Graphite powder was dissolved in ethanol to form a dispersion with a ratio of 1.5 g nanographite powder: 10 mL ethanol, and then the dispersion was placed in an ultrasonic machine so that the graphite powder could be evenly dispersed in the ethanol. Use a rubber-tipped dropper to evenly apply the dispersion after ultrasound on the substrate surface, using 1 mL of dispersion corresponding to a 80×80 mm 2 The nickel substrate is dried until there are no particles on the surface of the nickel substrate and the substrate surface is not exposed, and then placed in a ventilated place to dry for 5 minutes.

[0041] (2) Laser-induced graphene formation The nickel substrate coated with graphite powder was placed in a vacuum chamber and argon gas was introduced for 40 minutes to ensure that the air in the vacuum chamber could be completely exhausted to form an oxygen-free environment. The graphite powder coating was irradiated with laser again. The laser parameters were: spot size of 43 μm, number of processing times of 1, laser power of 1000 W, scanning speed of 1 mm / s, and continuous side blowing of argon gas for protection. The gas flow rate was controlled at 200 mL / min. After the laser irradiation was completed, the nickel substrate was taken out of the vacuum chamber and cooled for 30 minutes. A graphene film was formed in the laser irradiation area after the laser was removed, and a carbon source was implanted in the substrate as the basis for subsequent self-repair.

[0042] (3) Damage simulation For the graphene / nickel-based composite material grown once, the surface was polished with sandpaper of 400, 800, 1000, 1200, 1500, 2000 and 2500 meshes in sequence to ensure that the graphene film grown once could be completely destroyed, thereby simulating the extreme situation of friction and wear of graphene grown once on the nickel-based surface.

[0043] The graphene / nickel-based composite material after mechanical polishing was subjected to ultrasonic cleaning to remove residual carbon particles on the nickel-based surface and reduce the errors in the experiment.

[0044] (4) Graphene regrowth The nickel substrate after ultrasonic cleaning was placed in a vacuum chamber and argon gas was introduced for 40 minutes to ensure that the air in the vacuum chamber could be completely exhausted to form an oxygen-free environment. Then, a secondary laser was introduced to irradiate the graphite powder coating. The laser parameters were: spot size of 43 μm, number of processing times of 1, laser power of 21 W, scanning speed of 25 mm / s, and argon gas was continuously blown from the side for protection. The gas flow rate was controlled at 200 mL / min. This process was repeated many times until graphene could not be regenerated by laser irradiation.

[0045] (5) Performance testing Antioxidation performance test: The graphene of each growth number was treated in a muffle furnace. The treatment conditions were that the sample was heated to 400 °C at a rate of 1 °C every 5 minutes, and then kept in static air for 2 hours. The sample was taken out and weighed. The oxidation weight loss method was then used to measure the mass loss before and after, and the change in surface oxygen content was analyzed by EDS spectrum.

[0046] Film-base bonding performance test: The graphene of each growth number was treated by ultrasound. The treatment conditions were ultrasound for 2 min, 5 min and 10 min. After stabilization, the changes in surface defects of the samples were observed.

[0047] Example 2 A method for self-repairing a damaged area of ​​a thin film multiple times by using laser-induced graphene comprises the following steps: (1) Substrate pretreatment The surface of the initial nickel block was mechanically polished with sandpaper of 400, 800, 1000, 1200, 1500, 2000 and 2500 meshes in sequence until it was smooth, then ultrasonically cleaned, and finally dried for use. Graphite powder was dissolved in ethanol to form a dispersion, with a ratio of 1 g nanographite powder: 16 mL ethanol, and then the dispersion was placed in an ultrasonic machine so that the graphite powder could be evenly dispersed in the ethanol. Use a rubber-tipped dropper to evenly apply the dispersion after ultrasound on the surface of the substrate, using 3 mL of dispersion corresponding to a 80×80mm 2 The nickel substrate is dried in a ventilated place for 15 minutes until there are no particles on the surface of the nickel substrate and the substrate surface is not exposed.

[0048] (2) Laser-induced graphene formation The nickel substrate coated with graphite powder was placed in a vacuum chamber and argon gas was introduced for 60 minutes to ensure that the air in the vacuum chamber could be completely exhausted to form an oxygen-free environment. Then, the graphite powder coating was irradiated with laser once again. The laser parameters were: spot size of 65 μm, number of processing times of 3, laser power of 2000 W, scanning speed of 25 mm / s, and continuous side blowing of argon gas for protection. The gas flow rate was controlled at 160 mL / min. After the laser irradiation was completed, the nickel substrate was taken out of the vacuum chamber and cooled for 30 minutes. A graphene film was formed in the laser irradiation area after the laser was removed, and a carbon source was implanted in the substrate as the basis for subsequent self-repair.

[0049] (3) Damage simulation For the graphene / nickel-based composite material grown once, the surface was polished with sandpaper of 400, 800, 1000, 1200, 1500, 2000 and 2500 meshes in sequence to ensure that the graphene film grown once could be completely destroyed, thereby simulating the extreme situation of friction and wear of graphene grown once on the nickel-based surface.

[0050] The graphene / nickel-based composite material after mechanical polishing was subjected to ultrasonic cleaning to remove residual carbon particles on the nickel-based surface and reduce the errors in the experiment.

[0051] (4) Graphene regrowth The nickel substrate after ultrasonic cleaning was placed in a vacuum chamber and argon was introduced for 60 minutes to ensure that the air in the vacuum chamber could be completely exhausted to form an oxygen-free environment. Then, a secondary laser was introduced to irradiate the graphite powder coating. The laser parameters were: spot size of 65 μm, number of processing times of 3, laser power of 30 W, scanning speed of 20 mm / s, and argon was continuously blown from the side for protection. The gas flow rate was controlled at 160 mL / min. This process was repeated many times until the graphene could not be regenerated by laser irradiation.

[0052] (5) Performance testing Antioxidation performance test: The graphene of each growth number was treated in a muffle furnace. The treatment conditions were as follows: the sample was heated to 450 °C at a heating rate of 1.5 °C / 5 min, then kept in static air for 0.5 h, and the sample was taken out and weighed. The oxidation weight loss method was then used to measure the mass loss before and after, and the change in surface oxygen content was analyzed by EDS spectrum.

[0053] Film-base bonding performance test: The graphene of each growth number was treated by ultrasound. The treatment conditions were ultrasound for 2 min, 5 min and 10 min. After stabilization, the changes in surface defects of the samples were observed.

[0054] Example 3 A method for self-repairing a damaged area of ​​a thin film multiple times by using laser-induced graphene comprises the following steps: (1) Substrate pretreatment The surface of the initial nickel block was mechanically polished with sandpaper of 400, 800, 1000, 1200, 1500, 2000 and 2500 meshes in sequence until it was smooth, then ultrasonically cleaned, and finally dried for use. Graphite powder was dissolved in ethanol to form a dispersion with a ratio of 1.1 g nanographite powder: 13 mL ethanol, and then the dispersion was placed in an ultrasonic machine so that the graphite powder could be evenly dispersed in the ethanol. Use a rubber-tipped dropper to evenly apply the dispersion after ultrasound on the surface of the substrate, using 2 mL of dispersion corresponding to a 80×80 mm 2 The nickel substrate is dried until there are no particles on the surface of the nickel substrate and the substrate surface is not exposed, and then placed in a ventilated place to dry for 10 minutes.

[0055] (2) Laser-induced graphene formation The nickel substrate coated with graphite powder was placed in a vacuum chamber and argon gas was introduced for 45 minutes to ensure that the air in the vacuum chamber could be completely exhausted to form an oxygen-free environment. Then, the graphite powder coating was irradiated with laser once again. The laser parameters were: spot size of 49 μm, number of processing times of 2, laser power of 1500 W, scanning speed of 15 mm / s, and continuous side blowing of argon gas for protection. The gas flow rate was controlled at 180 mL / min. After the laser irradiation was completed, the nickel substrate was taken out of the vacuum chamber and cooled for 30 minutes. A graphene film was formed in the laser irradiation area after the laser was removed, and a carbon source was implanted in the substrate as the basis for subsequent self-repair.

[0056] (3) Damage simulation For the graphene / nickel-based composite material grown once, the surface was polished with sandpaper of 400, 800, 1000, 1200, 1500, 2000 and 2500 meshes in sequence to ensure that the graphene film grown once could be completely destroyed, thereby simulating the extreme situation of friction and wear of graphene grown once on the nickel-based surface.

[0057] The graphene / nickel-based composite material after mechanical polishing was subjected to ultrasonic cleaning to remove residual carbon particles on the nickel-based surface and reduce the errors in the experiment.

[0058] (4) Graphene regrowth The nickel substrate after ultrasonic cleaning was placed in a vacuum chamber and argon gas was introduced for 45 minutes to ensure that the air in the vacuum chamber could be completely exhausted to form an oxygen-free environment. Then, a secondary laser was introduced to irradiate the graphite powder coating. The laser parameters were: spot size of 49 μm, number of processing times of 2, laser power of 25 W, scanning speed of 5 mm / s, and argon gas was continuously blown from the side for protection. The gas flow rate was controlled at 180 mL / min. This process was repeated many times until the graphene could not be regenerated by laser irradiation.

[0059] (5) Performance testing Antioxidation performance test: The graphene of each growth number was treated in a muffle furnace. The treatment conditions were as follows: the sample was heated to 420 °C at a heating rate of 1.2 °C / 5 min, then kept in static air for 1.2 h, and the sample was taken out and weighed. The oxidation weight loss method was then used to measure the mass loss before and after, and the change in surface oxygen content was analyzed by EDS spectrum.

[0060] Film-base bonding performance test: The graphene of each growth number was treated by ultrasound. The treatment conditions were ultrasound for 2 min, 5 min and 10 min. After stabilization, the changes in surface defects of the samples were observed.

[0061] Example 4 A method for self-repairing a damaged area of ​​a thin film multiple times by using laser-induced graphene comprises the following steps: (1) Substrate pretreatment The surface of the initial nickel block was mechanically polished with sandpaper of 400, 800, 1000, 1200, 1500, 2000 and 2500 meshes in sequence until it was smooth, then ultrasonically cleaned, and finally dried for use. Graphite powder was dissolved in ethanol to form a dispersion with a ratio of 1.3 g nanographite powder: 14 mL ethanol, and then the dispersion was placed in an ultrasonic machine so that the graphite powder could be evenly dispersed in the ethanol. Use a rubber-tipped dropper to evenly apply the dispersion after ultrasound on the surface of the substrate, using 1.5 mL of dispersion corresponding to a 80×80 mm 2 The nickel substrate is dried until there are no particles on the surface of the nickel substrate and the substrate surface is not exposed, and then placed in a ventilated place to dry for 8 minutes.

[0062] (2) Laser-induced graphene formation The nickel substrate coated with graphite powder was placed in a vacuum chamber and argon gas was introduced for 45 minutes to ensure that the air in the vacuum chamber could be completely exhausted to form an oxygen-free environment. The graphite powder coating was irradiated with laser again. The laser parameters were: spot size of 52 μm, number of processing times of 1, laser power of 1200 W, scanning speed of 10 mm / s, and continuous side blowing of argon gas for protection. The gas flow rate was controlled at 170 mL / min. After the laser irradiation was completed, the nickel substrate was taken out of the vacuum chamber and cooled for 30 minutes. A graphene film was formed in the laser irradiation area after the laser was removed, and a carbon source was implanted in the substrate as the basis for subsequent self-repair.

[0063] (3) Damage simulation For the graphene / nickel-based composite material grown once, the surface was polished with sandpaper of 400, 800, 1000, 1200, 1500, 2000 and 2500 meshes in sequence to ensure that the graphene film grown once could be completely destroyed, thereby simulating the extreme situation of friction and wear of graphene grown once on the nickel-based surface.

[0064] The graphene / nickel-based composite material after mechanical polishing was subjected to ultrasonic cleaning to remove residual carbon particles on the nickel-based surface and reduce the errors in the experiment.

[0065] (4) Graphene regrowth The nickel substrate after ultrasonic cleaning was placed in a vacuum chamber and argon gas was introduced for 45 minutes to ensure that the air in the vacuum chamber could be completely exhausted to form an oxygen-free environment. Then, a secondary laser was introduced to irradiate the graphite powder coating. The laser parameters were: spot size of 52 μm, number of processing times of 1, laser power of 24 W, scanning speed of 10 mm / s, and argon gas was continuously blown from the side for protection. The gas flow rate was controlled at 170 mL / min. This process was repeated many times until the graphene could not be regenerated by laser irradiation.

[0066] (5) Performance testing Antioxidation performance test: The graphene of each growth number was treated in a muffle furnace. The treatment conditions were to heat the sample to 410 °C at a heating rate of 1.1 °C every 5 minutes, and then keep it in static air for 1.5 hours. The sample was taken out and weighed. The oxidation weight loss method was then used to measure the mass loss before and after, and the change in surface oxygen content was analyzed by EDS spectrum.

[0067] Film-base bonding performance test: The graphene of each growth number was treated by ultrasound. The treatment conditions were ultrasound for 2 min, 5 min and 10 min. After stabilization, the changes in surface defects of the samples were observed.

[0068] Example 5 A method for self-repairing a damaged area of ​​a thin film multiple times by using laser-induced graphene comprises the following steps: (1) Substrate pretreatment The surface of the initial nickel block was mechanically polished with sandpaper of 400, 800, 1000, 1200, 1500, 2000 and 2500 meshes in sequence until it was smooth, then ultrasonically cleaned, and finally dried for use. Graphite powder was dissolved in ethanol to form a dispersion with a ratio of 1.4 g nanographite powder: 12 mL ethanol, and then the dispersion was placed in an ultrasonic machine so that the graphite powder could be evenly dispersed in the ethanol. Use a rubber-tipped dropper to evenly apply the ultrasonicated 80×80 dispersion on the substrate surface, using 2 mL of dispersion corresponding to a 80×80 mm 2 The nickel substrate is dried in a ventilated place for 12 minutes until there are no particles on the surface of the nickel substrate and the substrate surface is not exposed.

[0069] (2) Laser-induced graphene formation The nickel substrate coated with graphite powder was placed in a vacuum chamber and argon gas was introduced for 55 minutes to ensure that the air in the vacuum chamber could be completely exhausted to form an oxygen-free environment. The graphite powder coating was irradiated with laser again. The laser parameters were: spot size of 57 μm, processing times of 2, laser power of 1800 W, scanning speed of 20 mm / s, and continuous side blowing of argon gas for protection. The gas flow rate was controlled at 190 mL / min. After the laser irradiation was completed, the nickel substrate was taken out of the vacuum chamber and cooled for 30 minutes. A graphene film was formed in the laser irradiation area after the laser was removed, and a carbon source was implanted in the substrate as the basis for subsequent self-repair.

[0070] (3) Damage simulation For the graphene / nickel-based composite material grown once, the surface was polished with sandpaper of 400, 800, 1000, 1200, 1500, 2000 and 2500 meshes in sequence to ensure that the graphene film grown once could be completely destroyed, thereby simulating the extreme situation of friction and wear of graphene grown once on the nickel-based surface.

[0071] The graphene / nickel-based composite material after mechanical polishing was subjected to ultrasonic cleaning to remove residual carbon particles on the nickel-based surface and reduce the errors in the experiment.

[0072] (4) Graphene regrowth The nickel substrate after ultrasonic cleaning was placed in a vacuum chamber and argon was introduced for 55 minutes to ensure that the air in the vacuum chamber could be completely exhausted to form an oxygen-free environment. Then, a secondary laser was introduced to irradiate the graphite powder coating. The laser parameters were: spot size of 57 μm, processing times of 2, laser power of 27 W, scanning speed of 20 mm / s, and argon was continuously blown from the side for protection. The gas flow rate was controlled at 190 mL / min. This process was repeated many times until graphene could not be regenerated by laser irradiation.

[0073] (5) Performance testing Antioxidation performance test: The graphene of each growth number was treated in a muffle furnace. The treatment conditions were as follows: the sample was heated to 440 °C at a heating rate of 1.4 °C / 5 min, then kept in static air for 1.2 h, and the sample was taken out and weighed. The oxidation weight loss method was then used to measure the mass loss before and after, and the change in surface oxygen content was analyzed by EDS spectrum.

[0074] Film-base bonding performance test: The graphene of each growth number was treated by ultrasound. The treatment conditions were ultrasound for 2 min, 5 min and 10 min. After stabilization, the changes in surface defects of the samples were observed.

[0075] Example 6 A method for self-repairing a damaged area of ​​a thin film multiple times by using laser-induced graphene comprises the following steps: (1) Substrate pretreatment The surface of the initial nickel block was mechanically polished with sandpaper of 400, 800, 1000, 1200, 1500, 2000 and 2500 meshes in sequence until it was smooth, then ultrasonically cleaned, and finally dried for use. Graphite powder was dissolved in ethanol to form a dispersion with a ratio of 1.2 g nanographite powder: 11 mL ethanol, and then the dispersion was placed in an ultrasonic machine so that the graphite powder could be evenly dispersed in the ethanol. Use a rubber-tipped dropper to evenly apply the dispersion after ultrasound on the surface of the substrate, using 2.5 mL of dispersion corresponding to a 80×80 mm 2 The nickel substrate is dried in a ventilated place for 14 minutes until there are no particles on the surface of the nickel substrate and the substrate surface is not exposed.

[0076] (2) Laser-induced graphene formation The nickel substrate coated with graphite powder was placed in a vacuum chamber and argon gas was introduced for 50 minutes to ensure that the air in the vacuum chamber could be completely exhausted to form an oxygen-free environment. The graphite powder coating was irradiated with laser again. The laser parameters were: spot size of 63 μm, processing times of 3, laser power of 1600 W, scanning speed of 5 mm / s, and continuous side blowing of argon gas for protection. The gas flow rate was controlled at 200 mL / min. After the laser irradiation was completed, the nickel substrate was taken out of the vacuum chamber and cooled for 30 minutes. A graphene film was formed in the laser irradiation area after the laser was removed, and a carbon source was implanted in the substrate as the basis for subsequent self-repair.

[0077] (3) Damage simulation For the graphene / nickel-based composite material grown once, the surface was polished with sandpaper of 400, 800, 1000, 1200, 1500, 2000 and 2500 meshes in sequence to ensure that the graphene film grown once could be completely destroyed, thereby simulating the extreme situation of friction and wear of graphene grown once on the nickel-based surface.

[0078] The graphene / nickel-based composite material after mechanical polishing was subjected to ultrasonic cleaning to remove residual carbon particles on the nickel-based surface and reduce the errors in the experiment.

[0079] (4) Graphene regrowth The nickel substrate after ultrasonic cleaning was placed in a vacuum chamber and argon was introduced for 50 minutes to ensure that the air in the vacuum chamber could be completely exhausted to form an oxygen-free environment. Then, a secondary laser was introduced to irradiate the graphite powder coating. The laser parameters were: spot size of 63 μm, number of processing times of 3, laser power of 28 W, scanning speed of 15 mm / s, and argon was continuously blown from the side for protection. The gas flow rate was controlled at 200 mL / min. This process was repeated many times until graphene could not be regenerated by laser irradiation.

[0080] (5) Performance testing Antioxidation performance test: The graphene of each growth number was treated in a muffle furnace. The treatment conditions were as follows: the sample was heated to 430 °C at a heating rate of 1.3 °C / 5 min, then kept in static air for 1 h, and the sample was taken out and weighed. The oxidation weight loss method was then used to measure the mass loss before and after, and the change in surface oxygen content was analyzed by EDS spectrum.

[0081] Film-base bonding performance test: The graphene of each growth number was treated by ultrasound. The treatment conditions were ultrasound for 2 min, 5 min and 10 min. After stabilization, the changes in surface defects of the samples were observed.

[0082] Figure 1Schematic diagram of the method for self-repairing film damage areas multiple times by using laser-induced graphene disclosed in Example 1 of the present invention; it can be seen from the figure that, under the premise of successfully preparing graphene in situ by laser and injecting rich carbon sources into the Ni matrix, the graphene grown on the surface once is removed, and the Ni matrix surface is irradiated with laser again, graphene can be grown again. For the secondary growth process, the laser power is much lower than the first growth, so the secondary growth relies on the solid phase diffusion of carbon atoms, while the primary growth is liquid phase diffusion. The diffusion barrier of carbon atoms in the solid phase is high. After grinding and polishing, the initial state of C in Ni is as shown in the left figure after polishing, and the Ni matrix contains rich carbon atoms and some vacancies. As the temperature increases, the number of vacancies continues to increase. As shown in the right figure, once the laser irradiation surface is introduced, the temperature rises sharply, the vacancy concentration increases sharply, and the carbon atoms migrate from the inside of the matrix to the surface in the form of Schottky defect diffusion. It is an easy method to transport carbon atoms to the surface through Schottky defects, because once carbon atoms diffuse to the surface, they are in the most stable state, thereby realizing the self-repair function.

[0083] Figure 2 The Raman spectrum of the self-repairing graphene disclosed in Example 2 of the present invention; wherein (a) is the self-repairing graphene grown twice; (b) is the self-repairing graphene grown three times; (c) is the self-repairing graphene grown four times; (d) is the self-repairing graphene grown five times; (e) is the self-repairing graphene grown six times; (f) is the Raman spectrum of graphene; as shown in (f), the D peak is the defect peak at 1350 cm -1 Around, indicating the disorder of the material; the G peak is composed of C atoms sp 2 The main characteristic peak is caused by the in-plane vibration of -1 The 2D peak mainly reflects the interlayer stacking mode of carbon atoms in graphene, which is around 2700 cm -1About. Through (a) the peak positions of the three peaks coincide with the three characteristic peaks in the Raman spectrum of graphene, it can be concluded that the secondary growth on the surface of the nickel substrate is graphene. And the characteristic peaks of the secondary growth graphene have sharp peak shapes and high peak intensities, indicating good crystallinity and good overall quality of the secondary growth graphene. Through (b) the peak positions of the three peaks coincide with the three characteristic peaks in the Raman spectrum of graphene, it can be concluded that the tertiary growth on the surface of the nickel substrate is graphene. And the characteristic peaks of the tertiary growth graphene have similar peak shapes and peak intensities to the characteristic peaks of the secondary growth graphene, indicating that the growth of the tertiary growth graphene is similar to that of the secondary growth graphene. Through (c) the peak positions of the three peaks coincide with the three characteristic peaks in the Raman spectrum of graphene, it can be concluded that the quadruple growth on the surface of the nickel substrate is graphene, indicating that the substance grown on the substrate surface is still graphene. However, the D peak intensity of graphene is significantly increased, and the 2D peak intensity is significantly decreased, which indicates that the graphene film formed by the fourth growth has more defects and more layers; (d) The peak positions of the three peaks are consistent with the three characteristic peaks in the Raman spectrum of graphene oxide, showing that the material grown on the surface of the nickel substrate by five times is graphene. The peak shape and peak intensity of the characteristic peaks of the five-times grown graphene are similar to those of the four-times grown graphene, indicating that the growth of the four-times grown graphene is similar to that of the three-times grown graphene, with more defects and a higher number of layers. (e) It is found that compared with the three characteristic peaks in the Raman spectrum of graphene, the Raman spectrum of the laser six-times grown graphene does not have the same peak position as the former, indicating that the carbon atoms inside the substrate cannot precipitate to the surface to form a graphene film.

[0084] Figure 3 The SEM images of the self-healing graphene before and after oxidation disclosed in Example 3 of the present invention; wherein, (a) is before the first growth oxidation; (b) is after the first growth oxidation; (c) is before the second growth oxidation; (d) is after the second growth oxidation; (e) is before the third growth oxidation; (f) is after the third growth oxidation; (g) is before the fourth growth oxidation; (h) is after the fourth growth oxidation; (i) is before the fifth growth oxidation; (j) is after the fifth growth oxidation; it can be seen from the figure that after the self-healing graphene is oxidized, defects of varying degrees appear on the surface.

[0085] Table 1 shows the percentage of C / Ni / O atomic content on the surface of self-repaired graphene before oxidation; Table 2 shows the percentage of C / Ni / O atomic content on the surface of self-repaired graphene after oxidation. Combining Table 1 and Table 2, it is found that the oxygen content of self-repaired graphene of each growth number before and after oxidation does not change by more than 0.70 wt%, which fully demonstrates the good oxidation resistance of graphene on the sample surface.

[0086] Table 1 The percentage of C / Ni / O atoms on the surface of self-repaired graphene before oxidation

[0087] Table 2 The percentage of C / Ni / O atoms on the surface of self-repaired graphene after oxidation

[0088] Figure 4The optical microscope images of graphene at various growth times before and after ultrasonic vibration treatment in Example 3 of the present invention; wherein, (a) is before the first growth ultrasound; (b) is the first growth ultrasound for 2 minutes; (c) is the second growth ultrasound for 5 minutes; (d) is the second growth ultrasound for 10 minutes; (e) is before the second growth ultrasound; (f) is the second growth ultrasound for 2 minutes; (g) is the second growth ultrasound for 5 minutes; (h) is the second growth ultrasound for 10 minutes; (i) is before the third growth ultrasound; (j) is the third growth ultrasound for 2 minutes; (k) is the third growth ultrasound for 5 minutes; (l) is the third growth ultrasound for 10 minutes; (m) is before the fourth growth ultrasound; (n) is the fourth growth ultrasound for 2 minutes; (o) is the fourth growth ultrasound for 5 minutes; (p) is the fourth growth ultrasound for 10 minutes; (q) is before the fifth growth ultrasound; (r) is the fifth growth ultrasound for 2 minutes; (s) is the fifth growth ultrasound for 5 minutes; (t) is the fifth growth ultrasound for 10 minutes. As can be seen from the figure, the optical microscopy images of the graphene grown once before ultrasonic treatment and at different times of ultrasonic treatment in Figures (a), (b), (c), and (d) show that the number of defects has increased significantly and the surface wrinkle marks have weakened. However, the film still completely covers the nickel substrate, showing a relatively excellent film-base bonding strength. The optical microscopy images of the graphene grown twice before ultrasonic treatment and at different times of ultrasonic treatment in Figures (e), (f), (g), and (h) show that the uncovered area of ​​the film has increased slightly, showing good film-base bonding strength. The optical microscopy images of the graphene grown three times before ultrasonic treatment and at different times of ultrasonic treatment in Figures (i), (j), (k), and (l) show that the surface morphology of the graphene grown on the film has basically not changed after 2 minutes of ultrasonic treatment. However, after 5 minutes of ultrasonic treatment and 10 minutes of ultrasonic treatment, the black area covering the ablation marks, that is, the graphene film grown three times, has large pieces of detachment. In general, the graphene film grown three times showed excellent membrane-substrate bonding after 2 minutes of ultrasonic treatment, and showed poor membrane-substrate bonding after 5 minutes and 10 minutes of ultrasonic treatment. It can be seen from the optical microscopy images of the graphene grown four times before and after ultrasonic treatment at different times in Figures (m), (n), (o), and (p) that the graphene film grown four times showed the same situation as the graphene film grown three times. It can be seen from the optical microscopy images of the graphene grown five times before and after ultrasonic treatment at different times in Figures (q), (r), (s), and (t) that after 2 minutes and 5 minutes of ultrasonic treatment, the graphene film grown five times on the surface of the nickel substrate had a slight degree of shedding. However, after 10 minutes of ultrasonic treatment, the carbon particles on the surface basically disappeared and a large area disappeared, showing poor membrane-substrate bonding.

[0089] The core purpose of the present invention is to expand the application of graphene in the field of metal protection. A graphene film is grown in situ on the metal surface by laser, and a large amount of carbon source is implanted in the nickel matrix. The original graphene film is mechanically polished by the cross grinding method, and then polished by a polishing machine, so that the graphene film is completely destroyed, thereby simulating the extreme situation of the graphene grown once on the nickel-based surface being subjected to friction and wear. At this time, the carbon source in the body is re-precipitated by laser induction, forming a new graphene film on the surface to repair the damaged area. The present invention hopes to create a graphene film that can self-repair multiple times in practical applications, which will significantly reduce the cost of metal protection and significantly increase the metal protection time.

[0090] In summary, the present invention aims to provide a solution that combines technological innovation and practical value. Laser technology is used to implant a large amount of carbon source in the nickel body and generate a graphene film on the surface. Once the graphene surface is damaged, the carbon source in the body is re-precipitated by laser induction to form a new graphene film on the surface to achieve the purpose of multiple self-repair. The present invention focuses on the key technical issues of metal protection and provides a method for multiple self-repair of graphene films. It also brings substantial improvements to significantly reduce the cost of metal protection and significantly increase the protection time. This self-repair technology can be widely used in various fields that require high strength and high stability, such as electronic products, aerospace, and the automotive industry.

[0091] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for self-repairing a damaged film region multiple times using laser-induced graphene, characterized in that: The following steps are involved: A carbon coating is spin-coated on the surface of the pretreated nickel substrate, and a laser irradiation is performed once and a protective gas is blown sideways. After drying, a layer of graphene film is formed. The graphene film is mechanically ground, polished, cleaned and dried, and then a secondary laser irradiation is introduced under vacuum conditions to obtain a regrown graphene / nickel-based composite material. The above steps are repeated until no graphene / nickel-based composite material can be obtained after laser irradiation. The surface morphology changes of the graphene at each growth number are explored by conducting oxidation resistance tests and film-base bonding strength tests on the graphene at each growth number, and the self-repair of the damaged area of ​​the graphene film is determined.

2. The method for self-repairing a damaged film region multiple times using laser-induced graphene according to claim 1, characterized in that: The steps of pre-treating the surface of the nickel substrate include: mechanically grinding and polishing the surface of the nickel substrate with 400-2500 mesh sandpaper until it is smooth, then ultrasonically cleaning and drying.

3. The method for self-repairing a damaged film region multiple times using laser-induced graphene according to claim 1, characterized in that: The preparation method of the carbon coating comprises: dissolving graphite powder in ethanol to form a dispersion, and evenly spin-coating the dispersion after ultrasonication on the surface of the nickel substrate to obtain the carbon coating, adding 10-16 mL of ethanol to every 1-1.5 g of nano graphite powder; 2 Spin coat 1-3 mL of the dispersion onto the nickel substrate.

4. The method for self-repairing a damaged film region multiple times using laser-induced graphene according to claim 1, characterized in that: The drying time is 5-15 minutes; the protective gas is argon, and the introduction time of the protective gas is 40-60 minutes.

5. The method for self-repairing a damaged film region multiple times using laser-induced graphene according to claim 1, characterized in that: During the one laser irradiation, the spot size of the laser beam is 43-65 μm, the laser power is 1000-2000 W, the scanning speed is 1-25 mm / s, and the number of processing times is 1-3 times.

6. The method for self-repairing a damaged film region multiple times using laser-induced graphene according to claim 1, characterized in that: The mechanical grinding is to use 400-2500 mesh sandpaper to mechanically grind the surface of the graphene film through a cross grinding method, and then polish it with a polishing machine.

7. The method for self-repairing a damaged film region multiple times using laser-induced graphene according to claim 1, characterized in that: When the secondary laser irradiation was introduced, argon gas was introduced for 40-60 min, and the flow rate was controlled at 160-200 mL / min.

8. The method for self-repairing a damaged film region multiple times using laser-induced graphene according to claim 1, characterized in that: During the secondary laser irradiation, the spot size of the laser beam is 43-65 μm, the laser power is 21-30 W, the scanning speed is 5-25 mm / s, and the number of processing times is 1-3 times.

9. The method for self-repairing a damaged film region multiple times using laser-induced graphene according to claim 1, characterized in that: The antioxidant test method includes: heating to 400-450°C at a heating rate of 1-1.5°C per 5 minutes, and keeping the temperature for 0.5-2 hours.

10. The method for self-repairing a damaged film region multiple times using laser-induced graphene according to claim 1, characterized in that: The membrane-base bonding strength test includes: subjecting the graphene of each growth number to ultrasonic treatment for 2-10 minutes.